Immunocytochemical Study on Blood and Organ Suspension of Tiger Grouper (Epinephelus fuscoguttatus) Infected with Field Isolate of Viral Nervous Necrosis - Artanti Tri Lestari; Putu Eka Sudaryatma (Jurnal Sain Veteriner, 2014)
One potential marine cultures that have been developed and started to show the international market is grouper. Grouper culture can not be separated from factors that can affect disease and thwart cultivation. One of the diseases that has been reported by researchers is viral nervous necrosis (VNN) causing mass mortality in fish, especially grouper larvae and juvenile stadia. Laboratory of Balai KIPM kelas l Denpasar develop rapid diagnostic techniques, precise and accurate test using immunocytochemistry of blood and organs as one of the initial inspection. Tiger grouper sized 150-300 g as much as 50 and acclimatized, then 10 fishes used as controls, 40 fishes were injected with inoculum VNN 101.5 reared without water replacement cycle for ten days. Clinical observation and organ sampling performed 12 hours post-infection and consecutive every 12 hours. Blood samples and organs were collected for immunocytochemical (streptavidin-biotin) and a confirmatory test using RT - PCR using kit IQ -2000 VNN. Immunocytochemistry and RT-PCR showed positive results against VNN blood smears and suspensions organs of grouper fish with 24 hours post-infection . Based on the test results, the immunocytochemistry test on the blood and organ suspensions can be used as a detection technique VNN which is rapid, precise and accurate.